Substance use disorders - (:unkn) unknown (Nova Science Publishers, Inc., 2021)
In a time when addiction has become a global and growing public health problem with detrimental impacts on societies worlwide, it is more than necessary for contemporary health professionals to familiarize themselves with the basic concepts of substance use disorders. One substantial reason is that addiction and psychoactive substance use-related issues present in a wide range of medico-legal contexts within clinical settings. Among the most common examples of forensic practices are evaluations for addictions allegedly caused by inappropriate prescriptions; physicians' impairments due to substance abuse; civil law issues such as termination of the rights of addicted parents; and criminal law issues, including probation, coerced treatment, and evaluations for criminal responsibility. Aside from the theoretical struggles that result from the multifaceted nature of addictive phenomena, clinicians are also likely to confront numerous ethical dilemmas during their clinical assessment and decision-making process. These may include but are not limited to conflicts regarding confidentiality, legal responsibilities, the obligation to act in the best interests of the patient, and informed consent procedures. Taken together, clinicians need to have a basic knowledge of addiction medicine, which is imperative to deal with the most common forensic challenges in the daily practice, and maintain their adherence to ethical standards. © 2021 Nova Science Publishers, Inc.